Clinical supervisors' understanding of spirituality and spiritual care in nursing: A South African perspective (part 2) - Ntombizodwa S. Linda; Deliwe R. Phetlhu; Hester C. Klopper (Elsevier, 2021)
The article provides findings of understanding of clinical supervisors (CSs) on spirituality and spiritual care in nursing practice. These participants who taught nursing skills to nursing students who were registered for R425 SANC Nursing Curriculum. Revealed uncertainties regarding their implementation of spiritual care in clinical nursing. They expressed concernes that despite South African Nursing Council's espoused holistic approach to nursing, a gap still exist in SANC's holistic philosophy. This view is supported and by the lack of guidelines from the SANC. According to the participants lack of guidelines indicates failure of SANC in embracing spiritual care as a vital component of "holistic nursing".An exploratory interview-based qualitative design was used to explore understanding of spiritual care by CSs. The certificate no: 13/4/22 was granted by the University Higher Degrees Committee. Nine (n = 9) CSs were purposively selected to respond to one open-ended question, "what is your understanding of spiritual care in nursing". Participants were included if a written consent was obtained, had facilitated clinical learning for two or more semesters. Data were analysed using Tesch.Emerged themes from in-depth interviews with the clinical supervisors include: (i) defining spiritual care; (ii) current status of spiritual care in teaching and learning; (iii) benefits of spiritual care; and (iv) need for spiritual care. Each theme is described below to show how it contributed to the objectives of the study.Spiritual care is needed not only to demostrate the nurses' morality. But more importantly nurses are obliged to alleviate deep human suffering which are met possible through spiritual care on one hand. On the other hand they questioned "how holistic" is ''holistic nursing care'' without attending to the spiritual health of the patient or client.